FOXM1‐mediated NUF2 expression confers temozolomide resistance to human glioma cells by regulating autophagy via the PI3K/AKT/mTOR signaling pathway. Issue 5 (14th June 2022) - Guo, Liang; Wu, Zhangyi
Abstract : Glioma is the most common malignant tumor in the central nervous system and has a high mortality rate. Temozolomide (TMZ) is a widely used chemotherapeutic drug for glioma. NDC80 kinetochore complex (NUF2) is suggested to play a regulatory role in different cancers, but its specific function and mechanism in glioblastoma TMZ resistance remain unknown. NUF2, assessed by reverse transcription quantitative polymerase chain reaction (RT‐qPCR), was highly expressed in glioma cell lines. TMZ was used to treat cells to establish a TMZ‐resistant cell line. The potential functions of NUF2 in glioma were assessed using cell counting kit‐8 (CCK‐8) assays, colony formation assays, 5‐Ethynyl‐2'‐deoxyuridine (EdU) assays, flow cytometry, Western blotting, and a tumor xenograft model. The results showed that NUF2 knockdown attenuated malignant phenotypes of TMZ‐resistant cells and prevented tumor growth. Mechanistically, as luciferase reporter assays and chromatin immunoprecipitation (ChIP) as showed, Fox transcription factor M1 (FOXM1) had binding sites on the NUF2 promoter. Rescue assays demonstrated that FOXM1 upregulation counteracted the inhibitory effects of NUF2 depletion on the malignancies of TMZ‐resistant cells. This study demonstrates that FOXM1‐activated NUF2 promotes TMZ to human glioma cells by regulating proliferation, apoptosis, and autophagy.